E-138 Safety and feasibility of transradial approach for cervical carotid stenting for treatment of carotid-artery stenosis. (4th August 2020) - Almallouhi, E; Al kasab, S; Jabbour, P; Gooch, M; Sweid, A; Chalouhi, N; Chen, S; Li, Y; Peterson, E; Yavagal, D; Starke, R; Spiotta, A
Abstract : Background: Traditionally, cervical carotid artery stenting is done through transfemoral or transcarotid approach. However, access site bleeding remains a significant challenge in both techniques, with a rate of about 4% in recent studies. In this study, we explore the feasibility of using transradial approach for cervical carotid stenting as a potential alternative. Methods: We collected data from the prospectively maintained registries of 6 centers in the United States to include consecutive patients who underwent carotid stenting for treatment of symptomatic carotid-artery stenosis using transradial approach from October 2018 until June 2019. Collected data included baseline characteristics, procedural variables, whether there was a crossover to transfemoral access, and complications. Our primary outcome was the complication rate related to the access site. Results: A total of 19 patients were included in this study. Mean age was 68.6 (±8), and 5 (26.3%) were females. The right radial artery access was used in all cases. Stenting of the right cervical internal carotid artery was done in 15 (78.9%) of the cases. Regarding the antispasmodic regimen used, Verapamil was used in 2 cases, Nitroglycerin was used in 6 cases, and a combination of both was used in 11 cases. Between 2000–5000 units of heparin were administered intraarterially or intravenously immediately after obtaining the access. A 6-French sheath was used in 13 cases, a 7-French sheath in 3 cases, and in 3 cases, the guide catheter (AXS Infinity, Stryker, USA) was exchanged over a 7-French sheath. Regarding guide catheters used, Benchmark (Penumbra, USA) was used in 14 cases, AXS Infinity in 3 cases, and Envoy (Codman Neuro, USA) in 2 cases. Mean contrast dose required was 93.3 (±48.4), radiation exposure was 14603 (±26118) mGy, and procedure duration was 24.6 (±14.2) min. None of the included patients had a complication related to access site, and only one patient required a crossover to transfemoral approach because of a device-related complication. Conclusion: Transradial approach is a feasible and safe option for cervical carotid stenting. The complication rate in our study is lower than previously reported numbers for transfemoral and transcarotid carotid stenting, but larger-scale studies are needed to confirm our findings. Disclosures: E. Almallouhi: None. S. Al kasab: None. P. Jabbour: 2; C; Medtronic and MicroVention. M. Gooch: None. A. Sweid: None. N. Chalouhi: None. S. Chen: None. Y. Li: None. E. Peterson: None. D. Yavagal: 2; C; Medtronic Neurovascular, Cerenovus, Rapid Medical and Neuralanalytics. R. Starke: 2; C; Penumbra, Abbott, Medtronic, InNeuroCo and Cerenovus. A. Spiotta: 1; C; Penumbra. 2; C; Penumbra, Stryker, Cerenovus, Terumo.